Searching For Vitamin C, Vitamin D and COVID-19: a Google Trends Study - Samira Eshginia; Leila Khalili; Masoumeh Khalili (Golestan University Of Medical Sciences, 2021)
ABSTRACT Background and objectives: COVID-19 outbreak is characterized as a pandemic. Owing to the effect of this disease on people's lives, news about the methods of preventing and treating this disease is released every day. There have been some clinical data suggesting that vitamins C and D can be useful in treating patients with COVID-19 disease. In this study, we aimed to examine vitamin C and D searching trends in 10 countries and worldwide about the COVID-19 news based on the data on Google Trends. Methods: We surveyed the searches about vitamins C and D using some keywords on Google Trends from December 15, 2019 to April 29, 2020. Results: The number of searches increased after the release of news about the effect of vitamins C and D on COVID-19. Conclusion: The results suggest that as the news about the role of vitamins on infection prevention and treatment spreads, people become more interested in expanding their nutritional knowledge.